POLA TRANSPORTASI PENJUALAN IKAN NILA (OREOCROMUS NILOTICUS) DALAM MENUNJANG KESEJAHTERAAN PETANI PADA MASA PANDEMI DI KABUPATEN MUSI RAWAS - Sri Murtini; Rudiansyah Rudiansyah; Neksidin Neksidin (Jurnal Perikanan Darat dan Pesisir (JPDP), 2020)
Fish is one of the commodities needed by the community to meet the needs of animal protein which has high nutritional value, so that treatment is needed to maintain the quality of the fish so that it is still alive and fresh when marketed. The pandemic period becomes an obstacle to maintaining marketing patterns in the regions so that to support the economy and welfare of fish farmers, marketing is carried out by distributing them to other areas using transportation patterns. Transportation is a means for fish farmers to market fish to consumers. The purpose of this research is to describe the transportation pattern of shipping the harvested fish to the area, the process of keeping the fish alive, how long it takes to bring the fish to their destination. The method used in this research is a case study method and sampling using secondary data. The results of the research obtained information to distribute the yields of goldfish cultivation in Musi Rawas Regency using a pick-up car which has a carrying capacity of about 800 kg. the media used is a plastic fish bag using oxygen. The physiological condition of the fish after traveling about 7 hours is still categorized as very good, seen from the active movements of the fish, as well as the morphology of the fish such as eyes, scales, and giblets. The selling price of goldfish after reaching consumers is around Rp. 28,000 / kg . The price of fish is not always stable in the market, one of the causes is high feed prices, weather factors and distribution in the field